THE INTENSIVE TECHNOLOGY OF GROWING STRAWBERRIES UNDER COVER (World Science, 2022)
The intensive technology of growing strawberries under cover, the production of maximum yield in the greenhouses, the structure of strawberry beds, the preparation, composting and sterilization of the substrate, raising the seedlings of strawberry, comparative economic evaluation they are KEYWORDS reviewed in the article.